FOUR NEWER HORIZONS FOR THE TREATMENT OF METASTATIC RESISTANT PROSTATE CANCER - DR . ANITA SAMRAJ; DR . V.KRISHNAN (International Journal of Pharma and Bio Sciences, 2014)
Prostate cancer is the second most common tumor affecting the men, ranking next to non melanoma skin cancers. It is also the second most cause of cancer mortality among men , next to neoplasm’s of the lung. Significant earlier detection, improved surveillance increases the number of cancer prostate men detection at an earlier stage and various treatment options are being tried to improve prognosis . The objective of our article is to provide a comprehensive review of newer molecules of prostate cancer management.